Comparative study of antibacterial and haemolytic activities in sea bass. European eel and blackspot seabream. - Caruso, Gabriella; Maricchiolo, Giulia; Genovese, Lucrezia; De Pasquale, F.; Caruso, R.; Denaro, Maria Gabriella; Delia, Santi Antonino; Lagana', Pasqualina (2014)
Sea bass (Dicentrarchus labrax, Moronidae), European eel (Anguilla anguilla, Anguillidae) and blackspot seabream (Pagellus bogaraveo, Sparidae) were studied to check their mucus, blood sera and tissue samples for antibacterial and agglutinating activity against a variety of Gram negative and positive bacteria. Samples were also examined for their haemolytic properties against sheep red blood cells. The highest antibacterial activity was detected in the blood sera of blackspot seabream and European eel (against Vibrio alginolyticus) and in the kidneys of sea bass (against Photobacterium damselae subsp. piscicida). Haemolytic properties against sheep red blood cells were observed in the mucus of sea bass and blackspot seabream, as well as in the sera of eel and sea bass. The sera of sea bass and eel showed also agglutinating activity against Pseudomonas aeruginosa and Staphylococcus aureus; the mucus of sea bass was able to agglutinate isolates of Vibrio fluvialis, V. alginolyticus and A. hydrophila. The study suggested that the mucus secretions, biological fluids and organs of the examined fish species can be regarded as an interesting source of bioactive compounds with antibacterial and haemolytic properties.